Nilai Pendidikan Agama Hindu Dalam Tari Baris Jangkang Desa Pakraman Pelilit Nusa Penida - Lasyana Dewi, Ni Putu Ida; Sariani Binawati, Ni Wayan (Jayapangus Press, 2021)
Indonesia has a lot of cultural wealth in the form of art, including music, sound, painting, sculpture and dance. The dances that developed in Indonesia have various types and are unique in each region. Culture or art that develops in Indonesia, especially in Bali, has an important role, both as a supporter of religious rituals and as a medium of entertainment. Sacred dance faces challenges in the current era, mainly due to the increasing influence of tourism and the ever-growing dynamics of Balinese society. This gives rise to debate and negotiation regarding which dances should be reserved for sacred events and which may be performed as tourism entertainment. In response to this, it is important to inherit and preserve sacred dances that are danced in religious ritual ceremonies because they have many spiritual and philosophical values. Even though some dance arts have experienced extinction, it turns out that there are still several dance arts that remain strong and strong among the people of Nusa Penida. One example is the Baris Jangkang Dance which can be found in Desa Pakraman Pelilit, Nusa Penida, Klungkung. This research uses a descriptive qualitative method, where the data that is processed and analyzed is presented in words arranged into a sentence. The history of this dance comes from the story of a person from Desa Pakraman Pelilit who had supernatural powers named I Nyoman Kulit. This dance contains educational values from a Hindu perspective. These values should be passed on to society as a basis or guide for life so that they have a clear direction and purpose in life. It has religiosity values from the aspect of the purity of the dancers and also the symbols of the clothing used. Has the value of education as a unifier of society.